Evaluating the Etiology and Hematological Profile of Bicytopenia and Pancytopenia in Pediatric Patients - Mahajan, Nikhil (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Bicytopenia and pancytopenia in children can result from various underlying conditions, including bone marrow disorders, infections, and nutritional deficiencies. Understanding the etiological and clinico-hematological profile is crucial for timely diagnosis and management. Objective: To evaluate the etiological factors and hematological profiles in children presenting with bicytopenias and pancytopenias. Material and Methods: This study was conducted in the Department of Pediatrics at a tertiary care hospital. A total of 30 children aged 1 month to 14 years diagnosed with bicytopenia or pancytopenia were included. Clinical data, hematological parameters, and potential etiologies were recorded. Results: Out of the 30 patients, 18 (60%) had pancytopenia and 12 (40%) had bicytopenia. The most common etiologies identified were aplastic anemia (30%), followed by infections (23.3%). Hematological findings showed significant variations in hemoglobin levels, platelet counts, and white blood cell counts. Conclusion: Aplastic anemia was the leading cause of bicytopenia and pancytopenia in children. Identifying the underlying etiology is essential for appropriate management and improving outcomes. Keywords: Bicytopenia, pancytopenia, children, hematological profile and etiology